Transcriptomic analysis reveals importance of ROS and phytohormones in response to short-term salinity stress in Populus tomentosa - Zheng, Lingyu; Meng, Yu; Ma, Jing; Zhao, Xiulian; Cheng, Tielong; Ji, Jing; Chang, Ermei; Meng, Chen; Deng, Nan; Chen, Lanzhen; Shi, Shengqing; Jiang, Zeping (Frontiers in Plant Science, 2015)
Populus tomentosa (Chinese white poplar) is well adapted to various extreme environments, and is considered an important species to study the effects of salinity stress on poplar trees. To decipher the mechanism of poplar’s rapid response to short-term salinity stress, we firstly detected the changes in H2O2 and hormone, and then profiled the gene expression pattern of ten-week-old seedling roots treated with 200 mM NaCl for 0, 6, 12 and 24 hours (h) by RNA-seq on the Illumina-Solexa platform. Physiological determination showed that the significant increase in H2O2 began at 6 h, while that in hormone ABA was at 24 h, under salt stress. Compared with controls (0 h), 3991, 4603 and 4903 genes were up regulated, and 1408, 2206 and 3461 genes were down regulated (adjusted P-value ≤ 0.05 and |log2Ratio|≥1) at 6, 12, and 24 h time points, respectively. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway annotation revealed that the differentially expressed genes (DEGs) were highly enriched in hormone- and reactive oxygen species-related biological processes, including ‘response to oxidative stress or abiotic stimulus’, ‘peroxidase activity’, ‘regulation of transcription’, ‘hormone synthetic and metabolic process’, ‘hormone signal transduction’, ‘antioxidant activity’ and ‘transcription factor activity’. Moreover, K-means clustering demonstrated that DEGs (total RPKM value>12 from four time points) could be categorized into four kinds of expression trends: quick up/down over 6 h or 12 h, and slow up/down over 24 h. Of these, DEGs involved in H2O2- and hormone- producing and signal-related genes were further enriched in this analysis, which indicated that the two kinds of small molecules, hormones and H2O2, play pivotal roles in the short-term salt stress response in poplar. This study provides a basis for future studies of the molecular adaptation of poplar and other tree species to salinity stress.